2022
DOI: 10.1038/s41598-022-13350-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Sclerotinia sclerotiorum populations from sunflower and cabbage in West Azarbaijan province of Iran

Abstract: Sclerotinia sclerotiorum is one of the most destructive fungal pathogens infecting a wide array of plant species worldwide. Management of this pathogen relies on the coordinated use of fungicides and resistant host cultivars with other control measures, but the effectiveness of these methods requires knowledge of the genetic variability and structure of the fungal populations. To provide insight into the genetic diversity and structure of this pathogen in West Azarbaijan province of Iran, a total of 136 isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The S. sclerotiorum isolate P8 was previously collected from a naturally infected sunflower field in Salmas (Molaei et al, 2020) and was utilized in this study. Phenotypic and genotypic analyses indicated that this isolate exhibits high aggressiveness toward sunflower, displays a high growth rate on potato dextrose agar (PDA, 39 g/L, Merck, Germany), shows resistance to iprodione, and belongs to the intergenic spacer (IGS) haplotype 2 (IGS2; Faraghati et al, 2022; Molaei et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. sclerotiorum isolate P8 was previously collected from a naturally infected sunflower field in Salmas (Molaei et al, 2020) and was utilized in this study. Phenotypic and genotypic analyses indicated that this isolate exhibits high aggressiveness toward sunflower, displays a high growth rate on potato dextrose agar (PDA, 39 g/L, Merck, Germany), shows resistance to iprodione, and belongs to the intergenic spacer (IGS) haplotype 2 (IGS2; Faraghati et al, 2022; Molaei et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, the crops in the region are threatened by various fungi, particularly soil‐borne pathogens such as Sclerotinia sclerotiorum (Lib.) de Bary (Faraghati et al, 2022; Molaei et al, 2020). Traditional methods to control these pathogens are often inadequate, emphasizing the need for alternative or complementary strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this technique ensures that the ideal crosses made are free from contamination. The obtained information will help plant breeders develop better achene and oil-yielding local hybrids containing better oil quality (Faraghati et al, 2022). It is also a hope that the project will produce effective breeding material and potential sunflower hybrids.…”
Section: Introductionmentioning
confidence: 93%
“…However, other studies have suggested taking into account the structure imposed by the MCGs in addition to a set of molecular markers in population analyses ( Lehner and Mizubuti, 2017 ; Lehner et al, 2019 ; Silva et al, 2021 ). Over the past few years, the population structure of S. sclerotiorum has been extensively documented from different host crops and from different regions in the world ( Atallah et al, 2004 ; Sexton et al, 2006 ; Hemmati et al, 2009 ; Ekins et al, 2011 ; Attanayake et al, 2013 ; Clarkson et al, 2013 , 2017 ; Aldrich-Wolfe et al, 2015 ; Dunn et al, 2017 ; Panullo et al, 2018 ; Faraghati et al, 2022 ). In early studies, S. sclerotiorum populations exhibited a predominantly clonal population structure with low genetic diversity based on MCGs and DNA fingerprinting genotypes ( Kohli et al, 1992 ; Cubeta et al, 1997 ; Hambleton et al, 2002 ).…”
Section: White Moldmentioning
confidence: 99%